2016
DOI: 10.1080/17453674.2016.1267835
|View full text |Cite
|
Sign up to set email alerts
|

Similar migration in computer-assisted and conventional total knee arthroplasty

Abstract: Background and purposeComputer-assisted surgery (CAS) in total knee arthroplasty (TKA) has been used in recent years in the hope of improving the alignment and positioning of the implant, thereby achieving a better functional outcome and durability. However, the role of computer navigation in TKA is still under debate. We used radiostereometric analysis (RSA) in a randomized controlled trial (RCT) to determine whether there are any differences in migration of the tibial component between CAS- and conventionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…There has been controversy as to whether the long‐term survival of hybrid TKAs is better than that of cemented TKAs due to biologic durable cementless fixation of the femoral component. In Norwegian registries, the survival of hybrid TKAs was better than that of cemented TKAs at 11 years of follow‐up [23]. A long‐term retrospective study with a minimum 15 years of follow‐up showed a better survival rate for aseptic loosening in hybrid TKAs compared with cemented TKAs [23].…”
Section: Discussionmentioning
confidence: 99%
“…There has been controversy as to whether the long‐term survival of hybrid TKAs is better than that of cemented TKAs due to biologic durable cementless fixation of the femoral component. In Norwegian registries, the survival of hybrid TKAs was better than that of cemented TKAs at 11 years of follow‐up [23]. A long‐term retrospective study with a minimum 15 years of follow‐up showed a better survival rate for aseptic loosening in hybrid TKAs compared with cemented TKAs [23].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Rhee et al [6] using nine RCTs with long-term follow-up confirmed this assumption by finding no differences in functional outcomes and survivorship between CAS and conventional TKA [6]. The findings of these RSA-based studies [4,9] are supportive of the main findings of Hickey et al [1] in that they suggest there is likely to be little, if any, clinical benefit from robotic surgery in terms of the clinically important endpoint of tibial revision.…”
mentioning
confidence: 78%
“…To our knowledge, two randomized controlled trials (RCTs) [4,9] on computer-assisted surgery (CAS) in TKA used RSA to measure tibial baseplate migration. van Strien et al [9] and Petursson et al [4] studied the effect on tibial baseplate migration 2 years after surgery randomizing 57 and 54 patients, respectively. They found no clinically relevant differences in tibial migration.…”
mentioning
confidence: 99%
“…An interesting randomized controlled trial from Petursson et al. (2017) showed no benefit in regard to RSA migration patterns, i.e. no signs of improved implant survival despite better positioning.…”
Section: Computer-assisted Surgerymentioning
confidence: 99%